Dis/Integrating cultural difference in practice and communication: A qualitative study of host and migrant Registered Nurse perspectives from New Zealand. (July 2018) - Brunton, Margaret; Cook, Catherine
Abstract: Background: Several earlier studies have provided evidence of the difficulties nurses have had adapting to foreign workplaces, however few have considered wider perspectives of the workplace communication environment. Objective: The aim of this study was to examine the viewpoints and experience of both New Zealand qualified nurses and internationally qualified nurses in managing communication within teams and the clinical practice context in an increasingly diverse healthcare workplace in New Zealand. Design: Interviews with 53 nurses currently employed in the New Zealand healthcare sector were carried out over a period of 15 weeks to gain insight into their intercultural experiences and how they responded. The transcripts of the interviews were analysed thematically. Setting: The interviews were all held outside working hours in venues and at times nominated by respondents. Participants: There were 53 participants (17 New Zealand registered nurses and 36 internationally qualified nurses) in the study. Respondents were nurses working in the health care sector who answered a call for participation in the study from an advertisement in the national nursing journal Kai Tiaki. Methods: A structured interview schedule was developed from the literature. The questions focused on cultural challenges and benefits, sources of learning, value-based differences accompanied by a description of critical incidents that were reflective of those events. Results: Qualitative thematic analysis of the data resulted in three primary themes: a polarized workplace (loss and learning); ethnocentrism 'othering' and empathy; and value based conflict. The results were discussed with a focus group of available respondents to verify the findings. Conclusion: All nurses in this study struggled with a care-rationed work environment, complicated by increasing diversity in both patients and staff. Despite evidence of conflict and misunderstanding, nurses also appeared willing to learn to adapt to enhance their practice. However, this process requires opportunities and resources to facilitate mutual understanding and accommodation to occur. The alternative of maintaining the status-quo will remain costly in terms of retention problems, the extent to which teams collaborate, and the contribution of insider-outsider divisions to sentinel events.